Nonlinearity of exciton polaritons in perovskite microcavities - Wu, Jinqi (Nanyang Technological University, 2023)
Exciton-polaritons are hybrid quasiparticles that stem from the strong coupling between microcavity photons and excitons. Their photonic component attributes an extremely small effective mass, while the nonlinear behavior inherited from the excitonic component provides the polaritons with unique physics. Recent progress in room temperature (RT) perovskite microcavities has advocated great promise in robust and nonlinear polaritons. My work concerns the nonlinearity of CsPbBr3 perovskite polaritons towards future optoelectronic applications at room temperature. In chapter 1, I would briefly introduce the backgrounds and basic knowledge of excitons, cavity photon dispersions, exciton polaritons, polariton nonlinearity and CsPbBr3 perovskite. In chapter 2, the experiment setup including CVD, AFM, SEM, EBL, evaporator, and spectroscopy are described. In chapter 3, I present the synthesis and characterization of CsPbBr3 perovskite film. In chapter 4, I demonstrate the first observation of the nonlinear regime of polariton-polariton interaction in perovskite exciton-polaritons. By designing a thick lead halide perovskite microcavity with multiple polariton branches, driven by an exciton-polariton condensation in one polariton branch, we find correlated polariton pairs at high k states in an adjacent branch. In chapter 5, we present an on-chip perovskite polariton parametric oscillator with a low threshold. By designing the lead halide perovskite thin film in a transparent microcavity, under the resonant excitation at a range of angles, the signal at the ground state with long wavelength and the idler at high k state are obtained thanks to the S-shaped polariton dispersion. In chapter 6, I conduct the direct precise measurement of polariton interaction strength in planar all-inorganic perovskite microcavities and enhance the polariton interaction strength value among confined 0D polaritons. In chapter 7, I report the first experimental demonstration of the high order topological polariton corner state lasing. By utilizing a two-dimensional Su–Schrieffer–Heeger (SSH) lattice of coupled perovskite micropillars, the high order topological corner states are obtained in perovskite polaritons, and the robust exciton polariton lasing is achieved at these corner states with low threshold at room temperature. This work drives the exploration of the interplay between the nonlinearity and topology of polaritons in future.